Influencia de apoyos, juntas y topes en la respuesta sísmica de puentes - Montufar Vieyra, Samuel (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
Present regulations for bridges construction and design, do not provide all the information needed for the incorporation of transverse shear keys and expansion joints effects in the seismic analysis of these type of structures. Frequently, destructive earthquakes have demonstrated the vulnerability of bridges as a result of the excessive movement beyond the available seat widths at expansion joints, causing the partial or total collapse of the superstructures, as well as the excess of transversal displacements of the deck causing misalignment of the axis of the bridge and bearing damage. This study aimed to explore the effect of transverse shear keys and expansion joint at abutments, in the global response of these structures, incorporating the contact non-linearity that occurs when the gaps of shear keys and expansion joints are closed during the seismic displacements. Time history seismic analysis of bridges under different configurations, type of supports, gap size and geometry. Was used to assess the impact of these elements in the bridge response. Eleven seismic ground motions were used as inputs for the simulation analysis. The suite of records was obtained from the UNAM seismic records data base, for sites located near the subduction zone of the Mexican Pacific Coast. The bridge response and performance comparison of the models was made in terms of ductility demand and spectral intensity. The ductility and capacity rotation of piers was also evaluated for the first yield, serviceability, and damage control limit states. The impact of the shear key gaps and pounding effects at the abutments was also studied. According to the seismic analysis results, it is concluded that the seismic shear keys effectively reduce transverse displacements, at the cost of increasing the demand and damage to piers, independently of the structural geometry.

En la actualidad los reglamentos para la construcción de puentes carecen de información apropiada para el modelado y el análisis sísmico de puentes, considerando el efecto de topes y juntas de dilatación. Con frecuencia se ha observado que estas estructuras llegan a presentar pérdida de longitud de asiento de la superestructura, provocando el colapso parcial o total de dichos puentes, así como también el exceso de desplazamientos transversales del tablero provocando desalineamiento del eje del puente y el daño en la superficie de rodamiento. El objetivo principal de este trabajo es el análisis del efecto de los topes sísmicos y las juntas de dilatación, en la respuesta global de estas estructuras, incorporando la no linealidad de contacto que se produce cuando las separaciones de topes y juntas se cierran durante los desplazamientos sísmicos. Se utilizaron análisis en la historia del tiempo para observar el comportamiento de los puentes bajo distintas configuraciones de apoyos y geometría. Los análisis se realizaron con la aplicación de registros sísmicos obtenidos de “La Red Acelerográfica del IINGEN de la UNAM”, para sitios ubicados cerca de la zona de subducción del Pacífico Mexicano. De acuerdo con los resultados de las distintas configuraciones de puentes se identificaron los estados límite de fluencia inicial, servicio y control de daño, para poder realizar una comparación global de los modelos en términos de ductilidad de rotación de las pilas, contra la intensidad espectral. Se estudió también el impacto que tiene la separación de topes y juntas en la respuesta del puente. De acuerdo a los resultados de los análisis sísmicos obtenidos, se llegó a la conclusión de que los topes sísmicos reducen efectivamente los desplazamientos transversales, a costa de incrementar la demanda y el daño en las pilas de los puentes, independientemente de su geometría.
Facultad de Ingeniería Civil. Maestría en Ingeniería en el Área de Estructuras
Keywords: info:eu-repo/classification/cti/7; FIC-M-2017-1153; Puentes; Topes sísmicos; Pérdida de asiento; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4075